Spiritual care for people suffering from dementia disorders – selected issues - Zurzycka, Patrycja; Wojtas, Katarzyna; Czyżowicz, Katarzyna (Nursing Problems / Problemy Pielęgniarstwa, 2020)
Spirituality as an integral part of human life has a significant impact on the understanding of disease, reactions associated with it, and decisions made in the treatment process. Therefore, it is important for effective therapeutic and care management. Spiritual care consti-tutes an important element of holistic nursing care focused on the needs of patients with dementia in cooperation with the therapeutic team, and it prevents depersonalisation of the patients, taking into account their psychosocial needs. Progressive dementia affects human functioning in terms of basic everyday activities and the possibility of self-care. If the care is focused solely on satisfying the patient’s biological needs, it often becomes task-oriented care and depersonalises the patient’s individuality, whose psychosocial needs are not taken into account. The knowledge of spiritual aspects of the patient’s functioning allows these issues to be included in the care and treatment plan, thus enhancing the effectiveness of the therapeutic process. Spiritual care is a valuable and integral element of holistic care, emphasising the broader aspect of humanity, and the recognition of spiritual needs alongside physical, social, and emotional needs involves the commitment and cooperation of all care providers. The aim of this paper was to present selected issues of spiritual care provided to patients suffering from dementia disorders. Selected issues were presented on the basis of available literature analysis. The approach to the individual needs of patients emphasises the holistic dimension of care. Spiritual care should be provided by the therapeu-tic team at every stage of contact with the patient.